Surgical Outcomes for Speech Surgery in 22q11.2 Deletion Syndrome: The Dilemma of Persistent Velopharyngeal Insufficiency After Pharyngeal Flap Operation. Issue 5 (July 2017) - Wagner, Ryan D.; Wolfswinkel, Erik M.; Buchanan, Edward P.; Khechoyan, David Y.
Abstract : Introduction: The majority of patients with 22q11.2 deletion syndrome suffer from velopharyngeal insufficiency (VPI). Patients with 22q11.2 deletion syndrome (22qDS) commonly present with a large central velopharyngeal gap in the setting of poor velar and pharyngeal wall motion. The posterior pharyngeal flap is considered the most effective technique to treat VPI in this complex patient group. This study aims to critically evaluate success rates of surgical management of VPI in 22qDS patients and discuss options for management of a failed posterior pharyngeal flap (PPF) with persistent VPI. Methods: A systematic review was performed through MEDLINE and Scopus to examine the outcomes of PPF surgery to treat VPI in patients with 22qDS. Complications were defined as persistent VPI, hyponasal speech, and obstructive sleep apnea. To demonstrate an approach to management, the authors outline a recent patient with a failed PPF in this patient population at the authors' institution. Results: The authors comprehensively reviewed 58 articles, 13 of which contained relevant information with extractable data. Of the 159 patients with 22qDS who underwent PPF to treat VPI, successful outcomes were reported in 135 patients (80%; range: 0%–100%). Complications were reported in 14% of patients, with need for revision operations in 3%. Discussion: Surgical management of VPI in patients with 22qDS is challenging, with variable success rates reported in the literature. If unsuccessful, the surgeon faces additional challenges with the revision surgery including a scarred PPF donor site, distorted palatal recipient site, and further medialization of internal carotid arteries. Surgical revision of a failed PPF requires meticulous preoperative planning and technical execution.